One Dimensional Water Flow through Snow. - Colbeck,Samuel C. (1971)
A theory is developed to describe the percolation of water through isothermal snow with a vertical porosity gradient. While the necessary laboratory experiments have not been done for snow, concepts from the general theory of two phase flow through porous media are used in the development. The general solution for the one-dimensional problem is given, which, when combined with any periodic boundary condition, can be used to make quantitative predictions. The theory is applied to water percolation through firn on the upper Seward Glacier. Using appropriate values for the parameters, theory shows a wave of volume flux which travels down into the firn and develops features similar to those observed by Sharp. These include an initially symmetric wave which distorts with depth, continuous (rather than intermittent) downward flow beneath the surface, and a decreasing value for the wave crest with depth. The theory predicts that the waves advance with a shock front which grows with depth. The shock front is thought to be only an approximation to the actual physical process. (Author)